2000
DOI: 10.1029/1999je001110
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of lunar surface maturity

Abstract: Abstract. The physical evolution of the lunar surface with exposure to the space environment is termed maturation, and maturity is the degree to which a particular lunar soil possesses quantitative characteristics consistent with that exposure. Several quantitative measures or indices of maturity have been proposed and employed, including the abundance of solar wind gas, abundance of various types of agglutinates, va:'ious measures of grain size, and ls/FeO. Among the changes attendant with space exposure are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
366
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 327 publications
(377 citation statements)
references
References 11 publications
7
366
3
1
Order By: Relevance
“…In contrast, low-thermal inertia anomalies are predominantly contained in the thousands of cold spots-vast disrupted regions surrounding~1 km and smaller fresh impact craters~100 kyr in age . Notably, all of these impact-related features are <1 Gyr old, explaining the general correlation of optical maturity (Lucey et al, 2000) and thermal inertia; features older than about a billion years have been erased by erosion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, low-thermal inertia anomalies are predominantly contained in the thousands of cold spots-vast disrupted regions surrounding~1 km and smaller fresh impact craters~100 kyr in age . Notably, all of these impact-related features are <1 Gyr old, explaining the general correlation of optical maturity (Lucey et al, 2000) and thermal inertia; features older than about a billion years have been erased by erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Lucey et al (2000) derived a quantitative optical maturity index (OMAT) based on observed spectral changes with age, which can be used to infer relative exposure ages of lunar surface materials. Although OMAT is known to be influenced by mineral composition and geologic setting, thermal inertia is not directly affected by composition (Fountain & West, 1970;Wechsler et al, 1972).…”
Section: Comparison To Albedo and Optical Maturitymentioning
confidence: 99%
“…S2), which is suggestive of a young age for the Chang'e-3 landing site. However, it has been noticed that there was no clear correlation between the optical maturity index and the ages of the Apollo mare soils (18).…”
Section: Mineral Abundances and Optical Maturity Indexmentioning
confidence: 99%
“…The estimated FeO contents are consistent with the APXS analyses within analytical uncertainties. The space weathering effect (darkening and reddening of the spectra) of the lunar soil can be indicated by the optical maturity index (18), which ranges from 0.098 to 0.158 with an exception of 0.312 for CD005 (SI Appendix, Table S2). The higher values of the optical maturity index and the spectral reflectance of CD005 may be due to blowing the top dusts off the lunar surface by the rocket during the descent of Chang'e-3 because CD005 is located closest to the lander (SI Appendix, Table S2).…”
Section: Mineral Abundances and Optical Maturity Indexmentioning
confidence: 99%
“…Using images collected while in lunar orbit from the Ultraviolet/Visible (UVVIS) camera (Kordas et al, 1995;McEwen and Robinson, 1997), scientist generated a detailed global multispectral mosaic and a series of mineralogy and maturity maps (Edwards et al, 1996;Robinson et al, 1999;Lucey et al, 2000a;Lucey et al, 2000b). To facilitate the mapping exercises, efforts were made to geodetically control the images into a global control network.…”
Section: Introductionmentioning
confidence: 99%